Composition of the essential oils of Origanum majorana and O. vulgare subsp hirtum growing wild in Turkey - Chalchat, M Ozcan, J C (Journal of Spices and Aromatic Crops, 2002)
The chemical composition of the essential oils isolated by hydrodistillation of the aerial parts of Origanum majorana L. and O. vulgare L. from Turkey has been examined by GC-MS. A total of 34 and 37 components were identified accounting for 97.80% and 98.61% of the oils of both O. vulgare and O. majorana, respectively. The oil of O. majorana contained carvacrol (43.12%), (E)-b-ocimene (13.03%), p-cymene (11.38%), linalool (10.07%) and thymol (4.46%) as main components. Major components of the O. vulgare oil were identified as carvacrol (48.38%), p-cymene (19.93%), y-terpinene (16.29%), p-caryophyllene oxyde (1.92%), p-caryophyllene (1.16%), linalool (1.58%) and myrcene (1.32%). It is shown that carvacrol was the dominant constituent of both oils.